TRANSFIGURATIONS OF THE COMPUTERIZED MATHEMATICS FINAL EXAM: HOW WAS THE RESULTS OF COMPUTERIZED ADAPTIVE TEST-BASED ASSESSMENT? - Rahim, Abdul; Hadi, Samsul; Marlina, Marlina; Susilowati, Dyah; Muti'ah, Muti'ah; Irhas, Irhas (Jurnal Pendidikan Matematika dan IPA, 2024)
Abstract Computerized Adaptive Test (CAT) allows the use of targeted tests, that is, each test taker obtains items that match his or her ability level. The purpose of this research is to find out the final semester exam with the CAT model. The research methodology is descriptive quantitative. Purposive sampling technique was used to take a sample of 73 students. The results of this study indicate that the CAT used in this semester final exam based on Moodle can select test items given to test takers adaptively according to the user's ability level. The very high ability category was 42 students, the high ability category was 11 students, the medium ability category was 9 students, the low ability category was 4 students, and the very low ability category was 7 students. Overall, the ability of learners is in the high category.